Comparing media and family predictors of alcohol use: a cohort study of US adolescents. Issue 1 (20th February 2012) - Stoolmiller, Mike; Wills, Thomas A; McClure, Auden C; Tanski, Susanne E; Worth, Keilah A; Gerrard, Meg; Sargent, James D
Abstract : Objective: To compare media/marketing exposures and family factors in predicting adolescent alcohol use. Design: Cohort study. Setting: Confidential telephone survey of adolescents in their homes. Participants: Representative sample of 6522 US adolescents, aged 10–14 years at baseline and surveyed four times over 2 years. Primary outcome measure: Time to alcohol onset and progression to binge drinking were assessed with two survival models. Predictors were movie alcohol exposure (MAE), ownership of alcohol-branded merchandise and characteristics of the family (parental alcohol use, home availability of alcohol and parenting). Covariates included sociodemographics, peer drinking and personality factors. Results: Over the study period, the prevalence of adolescent ever use and binge drinking increased from 11% to 25% and from 4% to 13%, respectively. At baseline, the median estimated MAE from a population of 532 movies was 4.5 h and 11% owned alcohol-branded merchandise at time 2. Parental alcohol use (greater than or equal to weekly) was reported by 23% and 29% of adolescents could obtain alcohol from home. Peer drinking, MAE, alcohol-branded merchandise, age and rebelliousness were associated with both alcohol onset and progression to binge drinking. The adjusted hazard ratios for alcohol onset and binge drinking transition for high versus low MAE exposure were 2.13 (95% CI 1.76 to 2.57) and 1.63 (1.20 to 2.21), respectively, and MAE accounted for 28% and 20% of these transitions, respectively. Characteristics of the family were associated with alcohol onset but not with progression. Conclusion: The results suggest that family focused interventions would have a larger impact on alcohol onset while limiting media and marketing exposure could help prevent both onset and progression.